Operadores I-parcialmente múltiplo somantes: uma unificação dos conceitos de somabilidade absoluta e múltipla - Silva, Emanuelle Claudia da (2018)
In this work we investigate notions of somability and concepts related to absolutely or multiple multilinear operators. Initially, we developed and detailed the classical results of linear theory, and then presented concepts and main theorems related to absolute and multiple somability. After that, we investigated the multiple summing multilinear operators with several exponents whose concept is motivated by the Inequalities of BohnenblustHille Inequalities and Hardy-Litttlewood Inequalities, and we proved an inclusion result for this class of operators. Finally, we will work with the I-partial operators, which unify the somability concepts presented above.